Gregorio Sancianco, Colonial Tribute, and Social Identities: On the Cusp of Filipino Nationalist Consciousness - Aguilar Jr., Filomeno V.; (Archīum Ateneo, 2019)
Gregorio Sancianco, the author of El Progreso de Filipinas (1881), is an ephemeral figure in Philippine history. Although somewhat known for his defense of the native against charges of indolence, Sancianco advanced a penetrating critique of colonial tribute that generally has been ignored but to which thisarticle draws attention. Sancianco argued that tribute did not only negate the principle of assimilation, but it also divided the native population and provoked social antagonisms. The tribute’s abolition in 1884 rendered Sancianco’s historical position as transitional, straddling the creole nationalism of the 1860s and the ilustrados’ colonial nationalism of the 1880s. Sancianco’s critique of tribute anticipated nationalist consciousness.KEYWORDS: TRIBUTE • IDENTITY • SPANISH COLONIALISM • RACISM • NATIONALISM